PENGEMBANGAN MEDIA PEMBELAJARAN PROJECTED MOTION MEDIA PADA MATA PELAJARAN MULOK KEAGAMAAN SHOLAT DHUHA KELAS 4 SDN KARANGPAKIS 1 KABUH JOMBANG - Siti Rohanah; Mohammad Saat Ibnu Waqfin; Dian Alfin Nur (JoEMS (Journal of Education and Management Studies), 2020)
Education has been experiencing rapid development over the years. But there are still many things left behind from the development. For example, in terms of instructional media. Therefore, in this research, the researcher reviews about the research of learning media which starts from research problems as follow: how the process of developing learning media is, how the students respond and how the final outcome of the learning media development. From the Problems found by the researcher, namely learning that is still conventional, by using research and development research method, the researcher took sub material as a trial product to be developed. That is Duha prayer material in the fourth grade of SDN 1 Karangpakis Kabuh. In this research development, researcher used Borg’s and Gall’s theory which was carried out by several stages. Those are preliminary studies, product design and development production. Before testing the product, the researcher first validated the experts, namely media experts and material experts, then tested for 27 respondents or students. Based on the stages that have been done, it can be concluded that the learning media projected motion in the subjects of religious mulok of duha prayer from material experts got an average value of 85.3% categorized as very feasible, from media experts got an average value of 93.7% categorized as very feasible, and from the response of the students got an average value of 93% categorized as very feasible. And the final result of the projected motion media learning is really feasible to be developed to the next stage in the learning process.